Case Report: Multimodal Imaging Guides the Management of an Eosinophilic Leukemia Patient With Eosinophilic Myocarditis and Intracardiac Thrombus - Jinping Si; Xinxin Zhang; Na Chen; Fangfang Sun; Ping Du; Zhiyong Li; Di Tian; Xiuli Sun; Guozhen Sun; Tao Cong; Xuemei Du; Ying Liu (Frontiers in Cardiovascular Medicine, 2022)
BackgroundEosinophilic leukemia (EL) is a rare, serious and potentially life-threatening condition characterized by the overproduction of eosinophils leading to tissue eosinophilic infiltration and damage. Although multiple organ systems may be involved, progressive eosinophilic myocarditis (EM) is the most common cause of morbidity and mortality. Early diagnosis and follow-up surveillance combined with multimodal imaging are crucial for appropriate treatment of EM.Case SummaryIt’s a rare case of EL with EM and intracardiac thrombus in a 59-year-old patient who presented with asthenia for 3 weeks. Full blood count analysis indicated significant eosinophilia. Bone marrow aspirate revealed dysplastic eosinophilia and a FIP1L1-PDGFRA fusion gene (4q12) was detected, confirming EL. Echocardiography revealed EM with intracardiac thrombus. This was later confirmed by cardiac magnetic resonance imaging. The patient was commenced on imatinib and prednisolone and good clinical response was obtained. Through 18F-FAPI PET/CT imaging, we obtained in vivo visualization of fibroblast activation changes in the early stage of cardiac structure remodeling. With anti-fibrotic therapy after heart failure, the patient achieved a good clinical response.ConclusionThis case demonstrates in vivo visualization of fibroblast activation after EM. Multimodality imaging can provide early diagnosis and may guide tailored antifibrotic therapy in early stage of EM.